Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1159/000323398
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glutamate Signal Evokes Gastric Juice Excretion in Dogs

Abstract: Background: Dietary-free L-glutamate (Glu) in the stomach interacts with specific Glu receptors (T1R1/T1R3 and mGluR1–8) expressed on surface epithelial and gastric gland cells. Furthermore, luminal Glu activates the vagal afferents in the stomach through the paracrine cascade including nitric oxide and serotonin (5-HT). Aim: To elucidate the role of dietary Glu in neuroendocrine control of the gastrointestinal phase of gastric secretion. Methods: In Pavlov or Heidenhain gastric pouch dogs, secretion was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In general, lipids strongly inhibit gastric emptying, so the lipid content of the test meal in the present study might have overcome the potential of MSG to accelerate gastric emptying. The effect of MSG on gastric juice secretion has been reported to be dependent on the nutritional composition of the test meal in dogs . Thus, glutamate not only accelerates GI motility but also has the potential to regulate glycemic homeostasis in a manner dependent on the co‐existing nutrients in a meal.…”
Section: Discussionmentioning
confidence: 99%
“…In general, lipids strongly inhibit gastric emptying, so the lipid content of the test meal in the present study might have overcome the potential of MSG to accelerate gastric emptying. The effect of MSG on gastric juice secretion has been reported to be dependent on the nutritional composition of the test meal in dogs . Thus, glutamate not only accelerates GI motility but also has the potential to regulate glycemic homeostasis in a manner dependent on the co‐existing nutrients in a meal.…”
Section: Discussionmentioning
confidence: 99%
“…L-glutamate also potentiates gastric secretion via the vagus nerve after binding to glutamate receptors (T1R1/T1R3 and mGluRs) located in gastric glands (Khropycheva et al 2011;Nakamura et al 2011;San Gabriel et al 2007;Uneyama et al 2006). As a result, single AAs from the diet not only add flavor but may also increase protein digestion efficiency.…”
Section: Peripheral Oral and Post-oral Aa Sensingmentioning
confidence: 99%
“…Recent reports have now shed new light on how free glutamate modulates gastric juice secretion. Khropycheva et al reported that the effect of dietary glutamate on the gastrointestinal phase of gastric secretion depended on the characteristics of the co-applied macronutrients [22,23]. Supplementation of glutamate to an amino acid-rich diet enhanced the secretion of acid, pepsinogen (inactive form of pepsin), and fluids in dogs with Pavlov pouches.…”
Section: Effects Of Dietary Free Glutamate On Gastric Secretionmentioning
confidence: 99%